Vlach communities in the border area between Croatia, Dalmatia and Bosnia from the French perspective - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2021)
Triplex Confinium is a term referring to the area of ​​the historical borderland of the Ottoman Empire, Venice and the Habsburg Monarchy, which existed from the beginning of the 15th century until the end of the 18th century. Most of the issues related to military settlement in Triplex Confinium, as well as the issues of the Vlach migrations in this area, have already been thoroughly researched by historians. This article summarizes these studies and compares them primarily with less known documents issued by the French administration in the years 1806–1813, when firstly Dalmatia, and later also Military Croatia, belonged to the Napoleonic Empire. The observations of French officers and officials made at the beginning of 19th century testify that the Vlach communities in this region evolved in different ways. The Vlachs from the Dalmatian interior (the Morlachs) retained their characteristic social structure (division into katuns), and traditional transhumant pastoralism remained their main economic activity. In turn, the social structures of the population of Military Croatia at the beginning of 19th century did not have much in common with the Vlach katun organization, because it was replaced by the military hierarchy. Moreover, traditional Vlach pastoral economy was replaced with agriculture.